Living and Learning: a Time-Budget Approach Exploring Daily Activity Patterns in Student Boarding House - Adiba, Ana; Kusuma, Hanson E (Universitas Muhammadiyah Surakarta, 2026)
Boarding houses are one of the most common types of accommodation used by university students, especially in urban cities. Student boarding house or Indekos represents a typical environment for students to balance their academic, personal, and social lives. Indekos function not only as places for resting and living but also as multifunctional spaces for studying, socializing, and performing daily routines. The current understanding of how students use time within these spaces remains limited, particularly in relation to their spatial behaviors, which leads to routine activites. The focus of this research is to identify the types of activities and duration performed by students in the boarding house or indekos using William Michelson's Time-Budget theory. Using mixed-methods approach, this study collected data through an open-ended questionnaire for the exploration of activity variables, which were then analyzed quantitatively using Factor Analysis (FA). From the results of preliminary exploration, it was found that students exhibit different activity patterns between weekdays and weekends. While the results of the latter analysis show that indekos serves dual roles: as efficient transitional spaces during weekdays and as flexible, restorative spaces on weekends. This study provides insights for the design of student boarding house or indekos that is more adaptive and compatible with their daily living patterns.